A statistical analysis of work-related accidents in women’s employment - Fatih Yilmaz (Masyarakat, Kebudayaan dan Politik, 2023)
Women are often victims of gender discrimination in various fields, including in the work environment. This research article aims to statistically evaluate the status of women’s employment and occupational accidents in some countries where regular data are available, and to provide predictions in the future. Using quantitative methods, data were analyzed with panel data analysis, bivariate correlation and two-step clustering methods. The findings of this study indicate that there is a positive and stronger correlation between work-injury for women than for men in all but a few developed social welfare countries. In some countries, while the correlation is negative for men, it is positive and strong for women. This study concludes that existing preventive regulations, including those in developed countries, are not sufficient to protect women. Women are more likely to work in non-traditional sectors where occupational health and safety (OHS) regulations are more flexible. Therefore, public authorities related to OHS should focus more on the conditions of this new industry in the future.